2011
DOI: 10.1016/j.ejvs.2011.04.037
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Approaches to Acute Aortic Type A Dissection: A CT-Based Feasibility Study

Abstract: Open repair of acute type A dissection is and remains the 'gold standard' of care. Our study demonstrates that approximately half the patients undergoing an open repair could potentially benefit from an endovascular repair. This new treatment option has not been evaluated to date.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
52
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(55 citation statements)
references
References 22 publications
1
52
1
1
Order By: Relevance
“…From an anatomical perspective, 30% to 50% patients with type A aortic dissection are amenable to TEVAR. 20,21 Thus, in the future more patients may be considered suitable for TEVAR with life-long follow-up. The ultimate goal is a fully catheter-based approach to repair the ascending aorta that minimizes procedural risk and initiates healing (as documented in type B dissections in which interventional entry closure is associated with thrombosis of the false lumen and favorable aortic remodeling).…”
Section: See Editorial Commentary Page S12mentioning
confidence: 99%
“…From an anatomical perspective, 30% to 50% patients with type A aortic dissection are amenable to TEVAR. 20,21 Thus, in the future more patients may be considered suitable for TEVAR with life-long follow-up. The ultimate goal is a fully catheter-based approach to repair the ascending aorta that minimizes procedural risk and initiates healing (as documented in type B dissections in which interventional entry closure is associated with thrombosis of the false lumen and favorable aortic remodeling).…”
Section: See Editorial Commentary Page S12mentioning
confidence: 99%
“…In 2000 Dorros et al reported the first case of type A aortic dissection managed with en endovascular technique through a transseptal approach [3], while Metcalfe et al described a case of endovascular repair of an acute type A dissection using an endograft designed for the ascending aorta introduced through the common femoral artery [5].…”
Section: Discussionmentioning
confidence: 99%
“…They report that, based on current device designs 32e50% of patients currently undergoing open repair for TAAD could potentially be candidates for endovascular repair. 15,16 [ Table 1]…”
Section: Morphological Suitabilitymentioning
confidence: 99%